Tren penelitian Keterampilan Komunikasi Terapeutik dalam Jurnal pendidikan Keperawatan di Seluruh Indonesia: dari Desain penelitian hingga Analisis - Lameky, Vernando Yanry (KAMBOTI: Jurnal Sosial dan Humaniora, 2022)
Communication skills are one of the goals to be obtained in 21st century education. This study uses content analysis on a collection of articles that have been researched in nursing education journals throughout Indonesia from 2006 to 2021, with emphasis on research on therapeutic communication skills. This research shows that in the last three years, the number of publications focusing on therapeutic communication skills has not progressed. In the collection of publications, the most types of research designed are quantitative, the research design is descriptive design to correlation research, the largest research subject is the patient and the main topic is the family with the most treatment, namely the relationship with the findings of this study, several recommendations are proposed for future research that support therapeutic communication as the main focus. Some of these recommendations include increasing the diversity of types of research and choosing more appropriate data analysis techniques.